'The machine runs itself': law is technology and Australian embryo and human cloning law. Issue 2 (3rd April 2021) - Goding, Vincent; Tranter, Kieran
ABSTRACT: Technology law scholarship has a tendency towards the dramatic. Technology causes disruption. Law must catch-up; it must ensure potential benefits from technology and avoid potential harms. There are even concerns that law, as an organiser of human life, is itself becoming eclipsed by forms of technological management. What is often not focused on is the practical process through which concerns about technology become transmuted into legal forms within specific jurisdictions. This paper examines the 23 years of Australian law concerning embryos and human cloning. Inspired by Carl Schmitt's criticism of modernity's political institutions and the laws they produce, what is identified is a machine that runs itself. It is shown to be a highly automated process whereby technical experts manage competing values. Rather than law regulating technology or technology regulating law; the Australian study suggests that law and its making, is technological.